Phase transition and microstructure investigation of perferritic isothermed ductile iron (IDI). (1st November 2020) - Landesberger, Martin; Koos, Robert; Erber, Maximilian; Pernumian, Matteo; Masaggia, Stefano; Hoelzel, Markus; Volk, Wolfram
ABSTRACT: Optical analysis, dilatometry as well as neutron diffraction are utilised to investigate the phase transition within ductile iron both in-situ and after the heat treatment process for perferritic isothermed ductile iron (IDI). A suitable annealing temperature is chosen by calculating a phase diagram for the investigated alloy. The phase transition which happens slightly above upper intercritical temperature is followed by neutron diffraction, while dilatometry elucidates the IDI microstructure evolution for cooling rates from 40 to 0.125 K/s. The dilatometry results are visualised in a CCT diagram and further investigated with metallography. An additionally used colour etching method is basis for discussing the formation of the pearlitic/ferritic network. The presence of 2 vol.-% of ferrite was sufficient to achieve the typical IDI microstructure. Finally, the cementite phase volume fractions and crystal structure are evaluated. . The lattice constants of ferrite and cementite were independent of the formed microstructure.